TRANSFORMASI SOSIAL EKONOMI MASYARAKAT PESISIR DAN PEDALAMAN DI KALIMANTAN; Mencari Sebuah Model Kebijakan Pembangunan Yang Memberdayakan (Socio-Economic Transformation for Coastal and Remote Society in Kalimantan: A Search for Enabling Developmenta - dan Thomas R. Hutauruk, Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2008)
The general picture of rural and coastal regions shows a unique phenomenon. On the one hand, they are traditionally thriving of natural resources. On the other hand, they are typically characterized as less-developed, isolated and marginalized community. Economic and social development indicators indicate that they has been lacking of basic service facilities as well as far from being well-informed society. Kalimantan, the biggest island in Indonesia, is also experiencing similar situation compared to its people. Development program and process in this region has frequently considered to be failed in leveraging people’s welfare and improving competitiveness of local products. Consequently, coastal and remote society remains deprived, elucidating how “vicious circle of poverty” works. In such a case, efforts of systemic transformation would be fruitful to overcome such complexities. The main idea is that public policy should function as trigger of the transformation wheel, both socially and economically. To support that notion, this paper offers 5 (five) categories of empowerment program that should be linked to 4 (four) sectors of development, namely economic, social and cultural, political and administrative, and infrastructure dimension. Another important thing is that acceleration of empowerment programs require political will of the government (both in central and local level) to burst through every single developmental-policy, innovatively. The utter goal of socio-economic transformation is the emergence of “good coastal, rural and remote governance”.  Key words : Coastal and hinterland society, Socio-Economic Transformation, Development program